THE COMPARISON OF PUPILS’ MATHEMATICAL PROBLEM SOLVING ABILITY IN THE CLASSROOM TAUGHT USING PROBLEMBASED LEARNING AND PROJECT BASED LEARNING MODEL IN GRADE SEVEN SMP NEGERI 2 PANAI TENGAH A.Y. 2015/ 2016 - Evan Dari Kristianto Simarmata; Syafari . . (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2016)
AbstractThe aim of this research is to study if pupils’ mathematical problem solving ability in the classroom that taught using Problem Based Learning (PBL) higher than in the classroom that  taught using Project Based Learning (PjBL). The population of this research is all pupils in class VII SMP Negeri 2 Panai Tengah. The sample of this research consists of twoclasses, namely, VII – 1 as the experiment class taught using PBL (30 pupils), VII – 2 as the comparison class taught using PjBL (31 pupils). The design of this research is posttestonly comparison group. The result of the research shows that the mean score are 54.07in experiment class and 41.32 in the comparison class; and tcalculation ≤ ttable, that is,1.327 ≤ 1.671 with significance level of 0.05 one tailed. It means that the pupils’ mathematical problem solving ability in the classroom taught using PBL model is not higher than in the class taught using PjBLmodel.Keywords: Mathematical Problem Solving Ability, Problem Based Learning, Project Based Learning